2018
DOI: 10.1002/chem.201802174
|View full text |Cite
|
Sign up to set email alerts
|

Non‐Covalent Interactions of a Neuroprotective Peptide Revealed by Photodissociative Cross‐Linking in the Gas Phase

Abstract: The small neuroprotective peptide Cys-Ala-Gln-Lys (CAQK) was selectively tagged with a diazirine group and its photochemical cross-linking was studied with model target peptides. Experimental results in combination with Born-Oppenheimer molecular dynamics revealed the structural preferences for binding to the amino acid residues in the target peptides. Effects of the target peptide sequence and N- and C-terminal modifications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…The resulting noncovalent complexes and photochemical products were analyzed using nano-ESI MS, which has the advantage of preserving noncovalent complexes. , A hybrid quadrupole time-of-flight mass spectrometer (q-TOF-MS, Maxis Impact, Bruker Daltonics, Bremen, Germany) was used for analysis . The MS/MS was performed for structural investigations by introducing nitrogen into the collision cell for CID of mass-selected complexes and reaction product ions.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting noncovalent complexes and photochemical products were analyzed using nano-ESI MS, which has the advantage of preserving noncovalent complexes. , A hybrid quadrupole time-of-flight mass spectrometer (q-TOF-MS, Maxis Impact, Bruker Daltonics, Bremen, Germany) was used for analysis . The MS/MS was performed for structural investigations by introducing nitrogen into the collision cell for CID of mass-selected complexes and reaction product ions.…”
Section: Methodsmentioning
confidence: 99%
“…The integrated relative intensities of these complex ions, (SL + H) + : (SL* + H) + : (SL**) + = 42:48:10 indicated similar affinities to peptide S of natural l -adrenaline compared to that of L*. The d -adrenaline complexes furnished a (SD + H) + : (SD* + H) + : (SD**) + ratio of integrated ion intensities equal to 51:46:3, slightly preferring natural d -adrenaline binding to peptide S. Overall, the results indicated that, compared to peptide–peptide noncovalent complexes, both the natural and tagged l - and d -adrenalines showed significant binding to peptide S upon electrospray ionization.…”
Section: Resultsmentioning
confidence: 79%
“…We were inspired by this finding, as well as by the previous gas-phase spectroscopic study, to design gas-phase adrenaline–peptide complexes for structure elucidation by a combination of UV photodissociation cross-linking (UVPD-X) and ion mobility mass spectrometry (IMMS). UVPD-X has been developed for structure analysis of noncovalent peptide–peptide and peptide–oligonucleotide complexes, relying on chromophore-selective photodissociation of diazirine-tagged noncovalent complexes produced in the gas phase by electrospray ionization (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Enrichment and digestion of modified peptides enables low protein concentrations to be used, minimising the possibility of aggregation or other aberrant interactions. Additionally, the custom UV LED platform enables PI‐XL on a 10 second timescale, not possible with arc‐based lamps, and only previously achieved using pulsed lasers in solution or in the gas phase . The low cost (≈$300) and simplicity of our UV LED system makes these timescales accessible to any researcher.…”
Section: Figurementioning
confidence: 99%